An episode of extremely low precipitable water vapour over Paranal observatory. Issue 1 (7th February 2014) - Kerber, F.; Querel, R. R.; Rondanelli, R.; Hanuschik, R.; van den Ancker, M.; Cuevas, O.; Smette, A.; Smoker, J.; Rose, T.; Czekala, H.
Abstract: We report on an episode of extremely low precipitable water vapour (PWV) of approximately 0.1 mm with a duration of more than 12 h at European Southern Observatory's Paranal observatory [2635 m above sea level (asl)]. Such conditions are more commonly expected at sites at much higher altitude such as ALMA on the Chajnantor plateau (5000 m asl) or otherwise particularly dry sites such as locations in Antarctica. We provide a full account of the measurements of PWV and other relevant atmospheric parameters. An explanation of the observed conditions is given in terms of the prevailing meteorological pattern. Based on statistical evidence from measurements by VLT spectrographs (UVES and CRIRES) covering more than a decade, we find that PWV <0.2 mm can be expected on less than 1 per cent of the nights, while <0.5 mm is encountered on 6–7 nights per year (≈ 2 per cent). The scientific potential of using this small but significant fraction of observing time is illustrated in the context of service mode observing.